Dpp/Gbb signaling is required for normal intestinal regeneration during infection - Zhou, Jun; Böttcher, Anna-Lisa; Kerr, Grainne; Boutros, Michael (Developmental biology, 2015)
Maintaining tissue homeostasis is a critical process during infection and inflammation. Tissues with a high intrinsic turnover, such as the intestinal epithelium, must launch a rapid response to infections while simultaneously coordinating cell proliferation and differentiation decisions. In this study, we searched for genes required for regeneration of the Drosophila intestine, and thereby affecting overall organism survival after infection with pathogenic bacteria. We found that Dpp/Gbb (BMP) signaling is essential for normal midgut regeneration, and that infection induces the BMP signaling ligands Dpp and Gbb. We demonstrate that Dpp is induced in visceral muscle and required for signaling activation. Subsequently, Gbb is induced in enterocytes after oral infection. Loss-of Dpp signaling in ISCs and transient committed progenitors called enteroblasts (EBs), or in EBs alone, led to a blockage in EC differentiation or maturation. Furthermore, our data show that down-regulation of Dpp signaling in the precursor cells including EBs also resulted in an increased number of abnormally small Pdm1-positive cells, suggesting a role of Dpp/Gbb signaling in EC growth. In addition, we show that Dpp/Gbb signaling acted downstream or in parallel to the Notch pathway to promote EC differentiation and growth. Our results suggest that Dpp/BMP signaling plays an important role in EBs to maintain tissue integrity and homeostasis during pathogenic infections.
Gesehen am 22.11.2017